Designing a Web-Based LMS at SMKN 4 Serang Using Express.js - Dody Naufal; Sigit Auliana; Gagah Dwiki Putra Aryono (Brilliance: Research of Artificial Intelligence, 2025)
The rapid advancement of digital technology in the education sector has transformed the learning process to become more efficient, flexible, and accessible. One of the innovations that support this transformation is the Learning Management System (LMS), which facilitates digital-based learning and improves interactions between teachers and students. However, SMKN 4 Kota Serang has not yet implemented an integrated LMS platform, resulting in limited support for Grade XII students in preparing for their final examinations. This research aims to design and implement a web-based LMS application using the Express.js framework to address these challenges and support digital learning needs. The development process follows the Waterfall methodology, which includes several sequential stages: requirement analysis, system design, implementation, testing, and maintenance. Data collection methods include observation, interviews, and literature studies to understand user needs comprehensively. The resulting system offers core features such as digital material management, assignment submission and grading, and a discussion forum to support structured communication between users. With the implementation of Express.js, the LMS application is developed to be fast, lightweight, and scalable, making it suitable for the school's environment. This system is expected to assist both teachers and students in conducting learning activities more effectively and efficiently. Overall, this research contributes to improving the quality of digital learning at SMKN 4 Kota Serang and provides a foundation for further system development in the future.